Determination of the Empathy Levels of Prospective Classroom Teachers: An Example of the Life Skills Teaching Course - Ütkür Nur (Acta Educationis Generalis)
Introduction: The concept of empathy has been described in many ways by researchers. According to some, it is the basic cognitive function or ability of being aware of others’ thoughts and feelings. Empathy refers to being able to respond to emotions, sharing the feelings of individuals, and reflecting them as if in a mirror. It also helps to establish good relationships with people, to understand them, and share their feelings. The use of empathy in the classroom, especially in life skills courses help students to make connections between school and everyday life.